Higher intakes of dietary vitamin D, calcium and dairy products are inversely associated with the risk of colorectal cancer: a case–control study in China. Issue 6 (28th March 2020) - Zhang, Xin; Fang, Yu-Jing; Feng, Xiao-Li; Abulimiti, Alinuer; Huang, Chu-Yi; Luo, Hong; Zhang, Nai-Qi; Chen, Yu-Ming; Zhang, Cai-Xia
Abstract: The effects of dietary vitamin D, Ca and dairy products intakes on colorectal cancer risk remain controversial. The present study investigated the association between these dietary intakes and the risk of colorectal cancer in Guangdong, China. From July 2010 to December 2018, 2380 patients with colorectal cancer and 2389 sex- and age-matched controls were recruited. Dietary intake data were collected through face-to-face interviews using a validated FFQ. Unconditional multivariable logistic regression models were used to calculate the OR and 95 % CI after adjusting for various confounders. Higher dietary vitamin D and Ca intakes were associated with 43 and 52 % reductions in colorectal cancer risk, with OR of 0·57 (95 % CI 0·46, 0·70) and 0·48 (95 % CI 0·39, 0·61), respectively, for the highest quartile ( v . the lowest quartile) intakes. A statistically significant inverse association was observed between total dairy product intake and colorectal cancer risk, with an adjusted OR of 0·32 (95 % CI 0·27, 0·39) for the highest v . the lowest tertile. Subjects who drank milk had a 48 % lower risk of colorectal cancer than those who did not (OR 0·52, 95 % CI 0·45, 0·59). The inverse associations of dietary vitamin D, Ca, total dairy products and milk intakes with the risk of colorectal cancer were independent of sex and cancer site. Our study supports the protective effects of high dietary vitamin D, Ca and dairy products intakes against colorectal cancer in a Chinese population.